Farm Ewe Flocks — Once-a-Year Lambing - Jones, Rodney D. (My University, 2005)
This publication provides an analysis of ewe flocks with once-a-year lambing in Kansas and the production level to be successful.
MF421_2005_10
Keywords: MF421; Economics; Livestock; MF